Stresses produced in an orthotropic half-plane under a moving line load. (1st December 2016) - Itou, Shouetsu
Abstract: The stresses and displacements of an orthotropic half-plane were obtained under a line load moving at a constant speed over its surface. The Fourier transform was applied to solve the problem at all speeds. It was verified that the stresses and displacements can be readily classified into three regimes according to the speed of the moving load. The expressions for the stresses and displacements have shapes similar to those of the solutions to the corresponding problem for an isotropic half-plane.